Türk din mûsikîsinin sağlıklı insanların hormonal yapıları üzerindeki etkileri - Arslan, Pınar (My University, 2016)
Bu araştırma Türk Din Mûsikîsinin sağlıklı insanların hormonal yapıları üzerindeki etkisinin incelenmesi amacıyla yapılmıştır. Örneklem gurubunu 49 kadın 54 erkek olmak üzere Kocaeli ilinde yaşayan 20-45 yaş aralığındaki toplam 103 sağlıklı birey oluşturmuştur. Mûsikî dinletilen gurup deney, dinletilmeyen grup ise kontrol gurubunu oluşturmaktadır. Deneklerden ilk safhada; bazal tükürük numunesi, ateş, nabız, tansiyon ölçülmüş ve anksiyete ölçeği yaptırılmıştır. İkinci safhada özel kulaklık vasıtasıyla akut stres sesi verilmiş ve tekrar tükürük alınmış, ateş nabız tansiyon ölçülmüş ardından anksiyete ölçeği yaptırılmıştır. Son aşamada ise deney grubuna Hüseynî makamında ney taksimleri ve ilahiler dinletilmiştir. Kontrol gurubuna ise son aşamada gözlerini kapatarak dinlenmeleri istenmiştir. Ardından ateş, nabız, tansiyon ve tükürük alınarak anksiyete ölçeği yaptırılmış, kayıt altına alınmıştır. Sonuçta; deney gurubundaki deneklerin mûsikî dinletisi sonrasında kortizol hormonu seviyelerinin düştüğü; kontrol grubundaki deneklerin dinlenme sonrasında kortizol hormonu seviyelerinde anlamlı farklılık oluşturmadığı görülmektedir. Kortizol, Müzik Terapi, Hüseynî Makamı

This study was conducted in order to study the effect of the Turkish Religious Music on the hormonal structures of the healthy subjects. The sampling group was formed of one hundred three (103) healthy individuals living in Kocaeli County whose, forty nine (49) of them were females and fifty four (54) of them were males. The group to whom music was listened was the experimental group and that who did not listen to the music was the control group. In the first stage; basal saliva specimen, fever, pulse, blood pressure were measured in subjects and anxiety scale was performed. In the second stage, acute stress sound was listened by means of a special earphone and again basal saliva specimen was taken and, fever, pulse, blood pressure were measured in subjects and anxiety scale was performed. In the last stage, reed flute improvisations in Hüseyni mode and hymns were listened to the experimental group. In the last stage the control group was requested to rest by closing their eyes. Subsequently, anxiety scale was performed by measuring fever, pulse, blood pressure and by taking saliva specimen and the results were recorded. In conclusion; it is observed that levels of cortisol hormone is decreased in the subjects included into the experimental group following the audition of music, but, no significant difference was found in the levels of cortisol hormone of the subjects included into the control group following the audition Kortizol, Müzik Terapi, Hüseynî Makamı
Keywords: Dini yönleri; İslam sanatı; Tarih; Türk musikisi